Big data, cloud and "bring your own device": how the data protection law addresses the impact of 'datafication' - Zulhuda, Sonny; Abdul Ghani Azmi, Ida Madieha; Hakiem, Nashrul (American Scientific Publishers, 2015)

(untitled)
Many hypes are currently surrounding the “datafication” such as the Big Data, Cloud and BYOD. The proliferation of data from ubiquitous sources is often not counter-balanced with adequate awareness and prudent risk management by the end-users, making it easier for others to take advantage of the new technology and reap from the abundant data available for all kinds of purposes including criminal. IT stakeholders should view Big Data not only as a new exciting technological advancement, but also a frontier full of potential risks to be addressed not only by industrial best practices, but also by the reforming laws in the area of information security and data privacy. This paper sets to undertake two major tasks. Firstly, examining the types of legal risks involved in the Big Data environment. Secondly, it highlights some aspects of data privacy and security laws already contained in the current data protection laws in Malaysia.